Some identities of generalized Fibonacci sequence - Chong C.-Y.; Cheah C.L.; Ho C.K. (American Institute of Physics Inc., 2023)
We introduced the generalized Fibonacci sequence Un defined by U0 = 0, U1 = 1, and Un+2x =x pUn+1+qUn for all p, q?Z+ and for all non-negative integers n. In this paper, we obtained some recursive formulas of the sequence. © 2014 AIP Publishing LLC.